Paleosalinity characteristics of the 1st member in the lower cretaceous prosopis formation, Baobab North Sag, Bongor Basin - Li, Xianbing; Xiao, Kang; Sun, Long; Wu, Shenghe; Xu, Zhenhua; Jiang, Sichong; Wu, Yuheng (Frontiers in Earth Science, 2024)
Paleosalinity is one of the important properties of paleolake water and is crucial for paleoenvironmental and paleoclimatic reconstruction. However, the paleosalinity characteristics of the 1st Member in the Lower Cretaceous Prosopis Formation (P1 Member) from the Baobab North Sag have not been systematically reported until now. In this study, 16 representative mudstone samples were collected from three coring wells and detailed elemental geochemical investigations were presented to reconstruct the salinity and water types for the P1 Member. The results show that the Sr/Ba ratios range from 0.32 to 0.93, indicating fresh water and brackish water, while the B/Ga ratios range from 1.6 to 3.4, also exhibiting the presence of fresh water and brackish water. The equivalent boron contents range from 84.3 ppm to 185 ppm, with the cast point located in the freshwater interval. Moreover, salinity values ranging from 1.2‰ to 11.0‰ for the Adams’ paleosalimeter and from 6.1‰ to 9.3‰ for the Couch’s paleosalimeter are indicative of brackish water, precisely mesohaline water. After sufficiently eliminating the interferences of diagenesis from the results, combined evaluation of evolutionary profiles and cross-plots of paleosalinity proxies suggest that the B/Ga ratio is the most important proxies for distinguishing water salinity types within the studied interval. The results of the B/Ga ratio indicate that the presence of two main water salinity types: fresh water (mainly distributed in the P14 and P12 sub-members) and brackish water (mainly distributed in the P13 and P11 sub-members). Furthermore, high salinity records in the study area correspond to arid climates, while low salinity intervals correspond to semi-arid and humid pulses, which provides a useful reference for the reconstruction of paleosalinity in terrestrial closed lake basins during the Cretaceous global warming period.